SUBSTITUSI JAMUR TIRAM PUTIH (Pleurotus ostreatus Jacq.) SEBAGAI PENGGANTI IKAN PADA PEMBUATAN GETAS - Irawan, Piter; Suyatno, Suyatno (Edible: Jurnal Penelitian Ilmu-ilmu Teknologi Pangan, 2017)
This study aims to determine the effect of substitution of white oyster mushroom (Pleurotus ostreatus Jacq.) As a substitute for fish in the manufacture of getas round. This research has been conducted in laboratory Faculty of Agriculture, University of Muhammadiyah Palembang in April 2016 until the month of February 2017. This study uses a randomized block design (RAK) are arranged in a nonfactorial with oyster mushroom substitution factor of five levels of treatment factors and repeated four times. The parameters observed in this study, for chemical analysis is the concentration of protein and moisture content. As for organoleptic tests include color, flavor, and aroma to test hedonic as well as the level of crispness with a ranking test on spherical brittle already fried. Substitution of white oyster mushroom (Pleurotus ostreatus Jacq.) Instead of fish highly significant effect on levels of protein and moisture content getas round. The protein content and the water content is highest at treatment P5 (oyster mushroom 90% and 10% starch) with an average value of 7.57% and 6.02%. While the protein content and low water levels in treatment P1 (oyster mushroom 10% and 90% starch) with an average value of 3.67% and 3.91%. The highest preference level value to the colors found in P1 treatment with an average value of 3.90 (criterion rather liked). Rated highest preference level of the flavor, aroma and crispiness level contained in P2 treatment with an average value of 4.10 (criteria like) and 3.95 (criterion rather liked) and 0.79 (crispy criteria once). To obtain a good getas round preferred by the panelists are advised to use the treatment P2 (white oyster mushroom 30% and 70% starch). For further research is recommended in the manufacture of ductile using other types of fungi that exist in Indonesia.